Comparison of the long‐term outcomes between proximal and distal IgG4‐related sclerosing cholangitis: A multicenter cohort study. Issue 4 (9th February 2023) - Cho, Sung Hyun; Song, Tae Jun; Park, Jin‐Seok; Yoon, Jai Hoon; Yang, Min Jae; Yoon, Seung Bae; Lee, Jae Min; Lee, Yun Nah; Kim, Seong‐Hun; Choi, Eun Kwang; Park, Se Woo; Oh, Dongwook; et al.
Abstract: Background and Aims: Immunoglobulin G4‐related sclerosing cholangitis (IgG4‐SC) is considered a biliary manifestation of IgG4‐related diseases. However, there has been a controversy on the clinical outcomes according to the location of the involved bile duct. We therefore compared the clinical outcomes and long‐term prognosis of IgG4‐SC with proximal bile duct involvement (proximal IgG4‐SC) and IgG4‐SC with distal bile duct involvement (distal IgG4‐SC). Methods: We reviewed the data of patients with IgG4‐SC that were prospectively collected at 10 tertiary centers between March 2002 and October 2020. Clinical manifestations, outcomes, association with autoimmune pancreatitis (AIP), steroid‐responsiveness, and relapse of IgG4‐SC were evaluated. Results: A total of 148 patients (proximal IgG4‐SC, n  = 59; distal IgG4‐SC, n  = 89) were analyzed. The median age was 65 years (IQR, 56.25–71), and 86% were male. The two groups were similar in terms of jaundice at initial presentation (51% vs 65%; P  = 0.082) and presence of elevated serum IgG4 (66% vs 70%; P  = 0.649). The two groups showed significant differences in terms of steroid‐responsiveness (91% vs 100%; P  = 0.008), association with AIP (75% vs 99%; P  = 0.001), and occurrence of liver cirrhosis (9% vs 1%; P  = 0.034). During a median follow‐up of 64 months (IQR, 21.9–84.7), the cumulative relapse‐free survival was significantly different between the two groups (67% vs 79% at 5 years; P  = 0.035). Conclusions: Relapse of IgG4‐SC frequently occurred during follow‐up. Proximal IgG4‐SC and distal IgG4‐SC had different long‐term outcomes in terms of steroid‐responsiveness, occurrence of liver cirrhosis, and recurrence. It may be advantageous to determine the therapeutic and follow‐up strategies according to the location of bile duct involvement.